2016
DOI: 10.4238/gmr.15038557
|View full text |Cite
|
Sign up to set email alerts
|

Number of repetitions for evaluating technological traits in cotton genotypes

Abstract: ABSTRACT. With the changes in spinning technology, technological cotton traits, such as fiber length, fiber uniformity, fiber strength, fineness, fiber maturity, percentage of fibers, and short fiber index, are of great importance for selecting cotton genotypes. However, for accurate discrimination of genotypes, it is important that these traits are evaluated with the best possible accuracy. The aim of this study was to determine the number of measurements (repetitions) needed to accurately assess technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These results are similar to the results observed by Matsuo, Sediyama [ 39 ] that evaluated the repeatability of oidium ( Erysiphe diffusa ) severity in several soybean genotypes. In addition, several studies revealed the efficiency of the principal component analysis based on the covariance matrix to estimate the repeatability coefficients for agronomic traits in perennial species [ 40 43 ] and annual species [ 44 – 46 ]. This type of analysis can help breeders, physiologists and phytopathologists to find experimental strategies to evaluate traits with accurate results.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to the results observed by Matsuo, Sediyama [ 39 ] that evaluated the repeatability of oidium ( Erysiphe diffusa ) severity in several soybean genotypes. In addition, several studies revealed the efficiency of the principal component analysis based on the covariance matrix to estimate the repeatability coefficients for agronomic traits in perennial species [ 40 43 ] and annual species [ 44 – 46 ]. This type of analysis can help breeders, physiologists and phytopathologists to find experimental strategies to evaluate traits with accurate results.…”
Section: Discussionmentioning
confidence: 99%